SOCIAL CONTROL OF TRADITIONAL LEADERS: EFFORTS TO MAKE TRADITIONAL VILLAGES AS A ROLE MODEL IN CRIME PREVENTION (STUDY IN CENTRAL KAMPUNG TRADITIONAL VILLAGE, SIAK DISTRICT) - Neri Widya Ramailis; Ema Fitri Lubis; Sobri . (E-Journal of Cultural Studies, 2024)
The purpose of carrying out this research is to seehow PatternSocial Control of Traditional Leaders: An Effort to Realize Traditional Villages as Role Models in Crime Prevention (Study in the Traditional Village of Kampung Tengah, Siak Regency)whether it has gone well based on an approach to social values, religion and customary law and culture in accordance with the social and cultural conditions of indigenous communities in the Kampung Tengah Traditional Village, Siak Regency.The method used in this research is a qualitative method with a descriptive approach using ethnographic analysis, where in a research activity more comprehensive, valid, reliable and objective data will be obtained. Data sources were obtained by taking 4 data collection techniques, namely by indexicality, reflexivity, and contextual action as well as taking documentation. From the results and discussion, it can be concluded that the pattern of social control that has been implemented by traditional leaders in Kampung Tengah to date is quite good, this can be seen in the aspect of prevention, efforts to overcome social problems and anticipate problems of deviant behavior and delinquency in children and adolescents by strengthening application of religious values, internalization of traditional, social and cultural values ??as aspects of prevention by increasing the Human Resources of children and adolescents (in the sense of having to go to school). It is not enough to stop there, building supporting facilities to stimulate what children and teenagers understand needs to be encouraged and executed by the village government and traditional leaders so that it is always directed towards useful and positive activities. Keywords:Social Control; Traditional Figures; Traditional Village; Role Models; Crime Prevention.